Feeling climate change to the bone: emotional topologies of climate. Issue 3 (21st March 2022) - Wright, Sarah; Plahe, Jagjit; Jack, Gavin
Abstract: This paper addresses climate change through collaborative work with social movement organisations in the Philippines. We contend that the tendency of work on climate change, social resilience and climate justice to ignore epistemological questions and proceed through technocentric dominant frames can lead to partial responses that support the status quo, contribute to slow (or fast) violence, and enhance ongoing processes of marginalisation. Instead, we argue, there is a need to co-develop analyses with those most affected. The experiences shared in this paper speak to complex knowings of climate and the intimate hurts of disaster, and provide rich scope for resistance and change. We find knowledges to be affective, emotional and relational, and deeply imbued with power relations. These insights lead us to theorise a topological angle on the knowings and beings of climate: to turn to emotional topologies. In seeking to elaborate on emotional topologies of climate, we draw on the concept of knowledge spaces to better understand meanings and practices of climate as emergent motleys of linked people, sites, affective process, activities and technologies. In the emergent nature of these spaces, there is scope for disruption, re-ordering and resistance.